In vitro evaluation of the early erosive lesion in polished and natural human enamel. Issue 9 (September 2018) - Mylonas, P.; Austin, R.S.; Moazzez, R.; Joiner, A.; Bartlett, D.W.
Highlights: In polished enamel, early acid erosion could be characterised using changes in: surface roughness, surface microhardness, surface reflectivity and surface morphology/texture. In polished enamel, statistically significant changes ( p < 0.01) in 3D step height could be detected after 60 s erosion. In natural enamel, early acid erosion could only be determined using changes in surface roughness and surface morphology/texture. Future work will focus on developing new early erosion models using natural enamel. Abstract: Objective: This study evaluated the capability of profilometry, microhardness, Optical Coherence Tomography (OCT) and Tandem Scanning Confocal Microscopy (TSM) in characterising the early erosive lesion in polished and natural human enamel in vitro. Methods: Polished (n = 60) and natural (n = 60) human enamel surfaces, were immersed and agitated in 0.3% citric acid erosion at 0 s, 10 s, 30 s, 60 s, 120 s, and 300 s (n = 10). Changes in the surface were measured with 3D-step height change (μm), surface roughness (μm), surface microhardness (KHN), and images were assessed qualitatively with OCT and TSM. Results: Mean (SD) 3D-step height change (μm) was measurable for polished enamel at: 60 s (0.24 ± 0.1), 120 s (1.16 ± 0.71), 300 s (2.01 ± 0.47; p < 0.05); a step height change was not detectable on acid challenged natural enamel surfaces. Mean (SD) surface roughness (μm) of polished enamel was detected at 10 s (0.270 ± 0.013; p < 0.05) and all erosion periods; and in natural enamel detected after 120 s (0.830 ± 0.125) and 300 s (0.800 ± 0.140; p < 0.005). Polished enamel Mean (SD) microhardness (KHN) statistically significantly decreased at all time points ( p < 0.001); this was unmeasurable for natural enamel. Qualitative image analysis of both surface types indicated erosive change at the surface level, with progression after increasing erosion time. Significance: The early erosive lesion in polished enamel could be characterised quantitatively surface roughness and microhardness and qualitatively using OCT and TSM; whilst in natural enamel only surface roughness could be utilised. Further investigation of early erosion in natural enamel is required to develop new more clinically relevant models.